A concept of mould spoilage prevention and acrylamide reduction in wheat bread: Application of lactobacilli in combination with a cranberry coating. (September 2018) - Bartkiene, Elena; Bartkevics, Vadims; Lele, Vita; Pugajeva, Iveta; Zavistanaviciute, Paulina; Mickiene, Ruta; Zadeike, Daiva; Juodeikiene, Grazina
Abstract: The current study evaluated the technological and antifungal properties of the newly isolated lactic acid bacteria (LAB) strains ( P. pentosaceus LUHS183, P. acidilactici LUHS29, Lactobacillus paracasei LUHS244, Lactobacillus brevis LUHS173, Lactobacillus plantarum LUHS135 and Leuconostoc mesenteroides LUHS242) and determined the influence of different LAB sourdoughs and their quantities (10, 15 and 20%) on wheat bread quality, including acrylamide content. In order to prolong the final products shelf life, LAB fermentation was combined with coating of the bread surface using cranberry preparations. All the tested LAB strains showed antifungal activities against Aspergillus nidulans, Penicillium funiculosum and Fusarium poae . L. brevis LUHS173 and Leu. mesenteroides LUHS242 strains showed weak antifungal activities, but good technological and acrylamide-lowering properties (the lowest acrylamide content (5.21 μg kg −1 ) in bread with 20% of LUHS173 sourdough was achieved). However, by increasing the sourdough content, the bread quality decreased (except Leu. mesenteroides LUHS242), therefore, additional experiments were undertaken, using a cranberries-based bread surface coating. This approach showed antifungal activities against Aspergillus fischeri, Penicillium oxalicum, P. funiculosum, F. poae, Alternaria alternata and Fusarium graminearum . Finally, selected LAB, in combination with an antimicrobial coating, leads to wheat bread with improved quality, safety and extended shelf life. Highlights: Concept for wheat bread moulding prevention and acrylamide reduction. LAB in combination with an antifungal cranberry coating for wheat bread preparation. The developed concept leads to bread with improved safety and extended shelf life.